Slack and the performance of state-owned enterprises - Stan, C.; Peng, Mike; Bruton, G. (Springer New York LLC, 2014)
Organizational slack has been recognized as critical to firm performance, although its impact is not always positive. Slack may be used to fuel innovation or alternatively excess resources may be squandered on pet projects. However, most research on slack is rooted in studying private firms in developed economies, especially the United States. Whether prior research on organizational slack can readily inform our understanding of state-owned enterprises' (SOEs) behavior is questionable since SOEs prioritize goals such as social welfare and full employment differently than do the privately owned enterprises (POEs). The differences between SOEs and POEs influence their sources and use of slack due to the nature of their ownership, budget constraints, and agency relations. To bring insight to this issue we develop an institutional change lifecycle model to study the relationship between slack and the economic and social aspects of SOE performance.